Uncertainty handling using neural network-based prediction intervals for electrical load forecasting - Quan, Hao; Srinivasan, Dipti; Khosravi, Abbas (Energy (Oxford), 2014)
The complexity and level of uncertainty present in operation of power systems have significantly grown due to penetration of renewable resources. These complexities warrant the need for advanced methods for load forecasting and quantifying uncertainties associated with forecasts. The objective of this study is to develop a framework for probabilistic forecasting of electricity load demands. The proposed probabilistic framework allows the analyst to construct PIs (prediction intervals) for uncertainty quantification. A newly introduced method, called LUBE (lower upper bound estimation), is applied and extended to develop PIs using NN (neural network) models. The primary problem for construction of intervals is firstly formulated as a constrained single-objective problem. The sharpness of PIs is treated as the key objective and their calibration is considered as the constraint. PSO (particle swarm optimization) enhanced by the mutation operator is then used to optimally tune NN parameters subject to constraints set on the quality of PIs. Historical load datasets from Singapore, Ottawa (Canada) and Texas (USA) are used to examine performance of the proposed PSO-based LUBE method. According to obtained results, the proposed probabilistic forecasting method generates well-calibrated and informative PIs. Furthermore, comparative results demonstrate that the proposed PI construction method greatly outperforms three widely used benchmark methods. •A new problem formulation for PI (prediction interval) construction is proposed for uncertainty handling.•Different PI assessment indices are compared together.•PSO is integrated into the LUBE (lower upper bound estimation) method named the PSO-based LUBE method.•Obtained results greatly outperform three widely used benchmark models.•Implementation of the proposed method is much easier and faster.